Do genes and environment meet to regulate cerebrospinal fluid dynamics? Relevance for schizophrenia - Palha, Joana A.; Santos, Nadine C.; Marques, Fernanda; Sousa, Joao C.; Bessa, João M.; Miguelote, Rui; Sousa, Nuno; Belmonte de Abreu, Paulo (Frontiers in Cellular Neuroscience, 2012)
Schizophrenia is a neurodevelopment disorder in which the interplay of genes and environment contributes to disease onset and establishment. The most consistent pathological feature in schizophrenic patients is an enlargement of the brain ventricles. Yet, so far, no study has related this finding with dysfunction of the choroid plexus (CP), the epithelial cell monolayer located within the brain ventricles that is responsible for the production of most of the cerebrospinal fluid (CSF). Enlarged brain ventricles are already present at the time of disease onset (young adulthood) and, of notice, isolated mild ventriculomegaly detected in utero is associated with subsequent mild neurodevelopmental abnormalities similar to those observed in children at high risk of developing schizophrenia. Here we propose that altered CP/CSF dynamics during neurodevelopment may be considered a risk, causative and/or participating factor for development of schizophrenia.